Family, social, and individual factors that contribute to the risk of drug abuse in adolescents (Damascus University Journal of arts and humanities sciences, 2025)
The research aimed to uncover the family, social and individual factors that contribute to the risk of drug abuse in adolescents. And to reveal the significance of the differences between the scores of addicted adolescents’ answers on the addiction factors scale according to the two variables: (gender and chronological age). The research adopted the descriptive approach, and a scale of addiction factors prepared by the researcher was applied. The research sample consisted of (54) addicted adolescents in Ibn Rushd Psychiatric Hospital. Among the most important results of the research: The most common factors that contribute to the risk of drug abuseamong adolescents were family factors, followed by social factors, then individual factors. There are no statistically significant differences between the average scores of the research sample members on the addiction factors scale due to the gender variable (males - females). There are statistically significant differences in the total score between the average scores of adolescent responses on the addiction factors scale in favor of addicted adolescents whose chronological age is (18-21 years old).
Keywords: Family; Drug Abuse; Adolescents; Social; Individual Factors